2017
DOI: 10.1016/j.jpeds.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Sedation, Analgesia, and Paralysis during Mechanical Ventilation of Premature Infants

Abstract: Objective To characterize administration of sedatives, analgesics, and paralytics in a large cohort of mechanically ventilated, premature infants. Study design Retrospective cohort study including all infants <1500 g birth weight and <32 weeks gestational age mechanically ventilated at 348 Pediatrix Medical Group neonatal intensive care units (NICU) from 1997–2012. The primary outcome is the proportion of mechanically ventilated days in which infants were administered drugs of interest. Multivariable logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…In contrast, Simons et al (morphine maintenance infusion, 10 µg/kg/h) did not observe lower blood pressure in morphine-exposed preterm neonates nor in inotropic prescription practices, irrespective of the post-menstrual age, within their randomized, placebocontrolled study (12). Finally, morphine delayed the attainment of full enteral nutrition (secondary analysis) by 3 days [17 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) in the placebo arm compared to 20 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) days in the morphine arm] in the NEOPAIN trial (13).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, Simons et al (morphine maintenance infusion, 10 µg/kg/h) did not observe lower blood pressure in morphine-exposed preterm neonates nor in inotropic prescription practices, irrespective of the post-menstrual age, within their randomized, placebocontrolled study (12). Finally, morphine delayed the attainment of full enteral nutrition (secondary analysis) by 3 days [17 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) in the placebo arm compared to 20 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) days in the morphine arm] in the NEOPAIN trial (13).…”
Section: Introductionmentioning
confidence: 94%
“…The reported short-term side effects associated to opioid exposure in preterm neonates include hypoventilation and apnea, low blood pressure, intestinal hypoperistalsis, and bladder dysfunction. Hypoventilation and apnea resulted in prolonged duration [7 (4-20) days in morphine-exposed group compared to 6 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days in the placebo group, + 1 day of ventilation] (9). Along the same line, Hartley et al recently reported that morphine (single oral, 100 µg/kg dose) in non-ventilated preterm infants, used to facilitate the screening for retinopathy of prematurity (ROP) in the Procedural Pain in Premature Infants (POPPI study) and to blunt the pain response, resulted in a high incidence (8/15 vs. 3/15, relative risk 2.7, number needed to harm = 3) of either newly occurring apneic events or an increase in the number of such events in the morphine-exposed group (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged pain has been shown to influence neonatal morbidity and have long-term adverse effects (8). However, there is still no consensus on the safety and efficacy of the drugs, especially opioids, used during neonatal mechanical ventilation (9). That is why our group decided to review the available evidence in the literature.…”
Section: Key Notesmentioning
confidence: 99%
“…However, guidelines caution against the routine use of opioids in common situations such as mechanical ventilation, given the potential for respiratory adverse effects 1. Despite this caution, opioid exposure for this indication remains common 2. Conflicting data exist regarding the impact of this exposure on the developing brain 3.…”
Section: Contextmentioning
confidence: 99%